A Study on Cultural Displacement In Bharati Mukherjee’S Novels: Uncovering the complexities of cultural identity in Bharati Mukherjee's novels (Journal of Advances and Scholarly Researches in Allied Education, 2014)
In her first novel, The Tiger's Daughter (1971),Mukherjee uses the return to India of her nostalgic and 'homesick' BengaliBrahmin heroine as the context for undermining national myths of origins andfoundations. In other words, the migrant's return 'to recover her roots' andthe stability of her cultural identity as an Indian is not equated uncriticallywith an unexamined sense of what being 'Indian' means.